The good quit: mastering the fine art of giving up - Lockwood, Jeffrey A., author; University of Wyoming Press, publisher (Colorado State University. Libraries, 2026)
Quitting is a vital and pervasive phenomenon that shapes our lives. The Good Quit is an enlightening and provocative challenge to the common perceptions around the choice to quit. Rather than offering simplistic how-to advice, scientist-turned-philosopher Jeffrey A. Lockwood makes full use of biological, psychological, and social sciences to unpack what constitutes quitting for the right reasons, at the right time, and in the right way, using both fundamental principles and concrete examples. He explores the full range of ways in which quitting can occur in the human experience, including addictions, careers, diets, games, habits, jobs, politics, relationships, religions, sports, and wars. Masterful quitting contributes to genuine success, but this practice nevertheless has been largely overlooked by scholars, teachers, coaches, and leaders. This book is a three-part exploration. In conceptual terms it asks, Is it really quitting if the decision is reversible, involuntary, or partial? In normative terms, it explores whether quitting must be well-reasoned, -timed, and -enacted to be justifiable. In applicable terms, it emphasizes phronesis, or "practical wisdom," and contributes to the understanding that what constitutes quitting, and doing so well, is vital to making decisions about whether to persevere or abandon difficult ventures. Flourishing is more complex than "grit-or-quit" advocates suggest. To thrive, we must come to know why, when, and how to quit. The Good Quit approaches this topic from an expansive and philosophical point of view, making it valuable for anyone contemplating the what, when, why, and how of quitting.
Section 1: How does quitting manifest? -- Section 2: What is it to quit? -- Section 3: Practical guidance.
Keywords: quitting; Employees -- Resignation -- Psychological aspects